Pemeriksaan Kesesuaian Kriteria Fungsi Jalan Dan Kondisi Geometrik Simpang Akibat Perubahan Dimensi Kendaraan Rencana - Angga Marditama Sultan Sufanir (Rekayasa Sipil, 2017)
Arterial, collector, and local are the hierarchy of road function in urban areas. Each of them is composed by primary and secondary road network. Certain road functions have certain criterion. Those criterion help in determining the type of design vehicle. Dimensionals and turning radius of the design vehicle are related to road geometric, i.e. the lane width and the widening of horizontal curve and intersection. The aim of this research is to check the suitability of road function criterion with the intersection geometric condition at Dipatiukur and Hasanuddin streets in Bandung. Those streets are chosen because they experience a change of the design vehicle dimension. Dipatiukur street has a secondary collector function, while Hasanuddin street has a secondary local function. Pd.T-18-2004-B, the guideline about a determination of road function classification in urban areas, stated that bus is not permitted to get through a local secondary road. In fact, DAMRI bus line 7 can get through Hasanuddin street. The result of checking the suitability of road function criterion can be seen from both design speed and the width of the road. If the vehicle designed is a car, it can be concluded that those two streets meet the requirements. Meanwhile, the result of checking the intersection geometric condition shows that the turning radius, entering sight distance, and the path for a bus are not appropriate with Pt.T 02-2002-B guideline about a Geometric Intersection Designing Procedure and a Geometric Designing Procedure for Inter-Urban Road Numb. 038/TBM/1997.